Effects of pre- and post-harvest konjac glucomannan phosphate ester composite film coating on the volatile profiles of mangoes during storage - Li, Xuehui; Zhang, Chen; Liu, Changrui; Luo, Weiqi; Wang, Ying; Wang, Libin; Abdullah, Norhafizah (Elsevier, 2024)
Post-harvest mangoes are prone to spoilage, and volatiles change accordingly. Konjac glucomannan phosphate composite film (KGMP), as an environmentally friendly polysaccharide-based material, has been shown to possess good film-formation, stability, antibacterial activity, and water vapor permeability. However, the impact of KGMP on the quality and aroma of mangoes during storage remains unclear. Therefore, KGMP was used to coat mangoes before and after harvest. Results indicated that KGMP delayed weight loss, the decline in firmness, and the deterioration of color difference. It also delayed the accumulation of total soluble solids, increased titratable acidity, limited ethylene evolution, and altered aroma quality. A total of 39, 40, and 31 volatiles were detected in JinHwang, Keitt, and Ivory, respectively. Changes in their contents were correlated with ethylene evolution. Although KGMP altered the formation of over 70% of mango volatiles, it had little effect on the total volatile abundance. Pre-KGMP treatment had a more pronounced inhibitory effect on volatile abundances but the increase of key volatiles like ethyl acetate, propyl propanoate, ethyl hexanoate suggested that KGMP treatment could enhance certain flavor characteristics while potentially extending the shelf life. Volatiles such as α-terpinene, diallyl disulfide, and α-phellandrene played key roles in differentiating mangoes under different conditions.